The Effect Of Tax Planning On Profit Management In Listed Companies In Jakarta Islamic Index Period 2016-2018 - Roni, Abdul (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Recognition of the value of tax planning and deferred tax expense provides management with the opportunity to practice revenue management. This study aims to determine how much influence tax planning and tax burden have on earnings management in companies listed on the Jakarta Islamic Index for the 2016-2018 period. The method used in this research is multiple linear regression. The population in this study were companies registered at JII for the 2016-2018 period, totaling 15 companies. The sampling technique used is purposive sampling. The type of data used is secondary data obtained from the company's published financial statements at www.idx.co.id. The data is processed through several statistical test methods of multiple linear regression using SPSS 18 software. Based on the results of statistical tests, it can be concluded that tax planning has a positive effect on earnings management, and deferred tax expense has a positive effect on the probability of companies making earnings management. This study finds that earnings management does occur to avoid reporting losses on companies listed on the Jakarta Islamic Index in 2016-2018.